Business simulation game for teaching multi-echelon supply chain management. (10th April 2010) - Merkuryev, Yuri; Merkuryeva, Galina; Bikovska, Jana; Hatem, Jonas; , Bram Desmet
This paper presents a new business game which helps to understand concepts developed in the ECLIPS project of the European Comission. The game provides an insight into different aspects of supply chain management, i.e., general supply chain mechanisms, non-cyclic and cyclic inventory replenishment policies. This allows for people who have no deep notion in this area to better understand project concepts and evaluate their efficiency in practice. Demonstrating concepts in a playful way is considered as more powerful and effective than purely explaining the underlying theory. The paper describes game rules, playing process and provides results of game test sessions.